Digital Adoption and Women in the Labor Market: Indonesia's Case - Sofa, Wahyuni Andriana; Eschachasthi, Realita (Universitas Airlangga, 2024)
Although the advantages of digitalization are frequently mentioned, there is still a persistent gender disparity in labor participation, especially in developing nations. This study examines the extent to which digitalization guarantees gender equality. Specifically, it aims to analyze the impact of internet usage on women's involvement in Indonesia's workforce. This study additionally examines the impacts in various parts of the country. Through the use of panel Tobit regression, utilizing district-level data obtained from SUSENAS-KOR, SAKERNAS, and INDO-DAPOER for the years 2017-2019, we have discovered a noteworthy and positive correlation between the utilization of the internet and the participation of women in the labor force. The observed effect remains strong even after accounting for additional factors. The heterogeneity analysis indicates that the correlation between internet usage and female labor force participation is more pronounced in the Java region than in areas outside Java. However, obstacles still prohibit women from accessing the advantages of digitalization. Hence, the proposed policy entails prioritizing equitable internet access and diminishing the obstacles to women's participation in the labor market to attain gender equality.